The random first-order transition theory of active glass in the high-activity regime. (1st November 2022) - Mandal, Rituparno; Nandi, Saroj Kumar; Dasgupta, Chandan; Sollich, Peter; Gov, Nir S
Abstract: Dense active matter, in the fluid or amorphous-solid form, has generated intense interest as a model for the dynamics inside living cells and multicellular systems. An extension of the random first-order transition theory (RFOT) to include activity was developed, whereby the activity of the individual particles was added to the free energy of the system in the form of the potential energy of an active particle, trapped by a harmonic potential that describes the effective confinement by the surrounding medium. This active-RFOT model was shown to successfully account for the dependence of the structural relaxation time in the active glass, extracted from simulations, as a function of the activity parameters: the magnitude of the active force ( f 0 ) and its persistence time ( τ p ). However, significant deviations were found in the limit of large activity (large f 0 and/or τ p ). Here we extend the active-RFOT model to high activity using an activity-dependent harmonic confining potential, which we solve self-consistently. The extended model predicts qualitative changes in the high activity regime, which agree with the results of simulations in both three-dimensional and two-dimensional models of active glass.